Kondisi Ekosistem Terumbu Karang di Pulau Gelasa Kabupaten Bangka Tengah - Wahyu Adi; Umam Kamarullah; Dedi Dedi; Hedi Sanjaya; Riko Ardyansah; Robi Gunawan; Muhammad Mahatir; Khudory Mustofa; Muhammad Rizqi Ramadhani; Sartini Sartini; Susi Susanti; Ety Febryanti; Khaeruddin Khaeruddin; Arham Hafidh Akbar; Sohibul Wafa Tadjul Arifin (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2020)
Coral reefs are a place of biological, chemical and physical cycles globally that have very high levels of productivity. Gelasa Island is a potential small island owned by the Bangka Belitung Islands Province. This island has the potential of fringing reefs that have not been used optimally. This aims of study to analyze the percentage of live coral cover in the coral reef ecosystem on Gelasa Island. The research was conducted in October 2019. The research location was Gelasa Island, Central Bangka Regency. The method used in this research is Line Intercept Transect (LIT). The results of the study, coral type of Gelasa Island is fringing reef in the form of reef flat. The percentage value of live coral cover on Gelasa Island ranged from 40.3 to 62.06%. Found as many as 20 types of lifeform and 20 genera of hard corals on Gelasa Island.